Amphibians of Vassununga State Park, one of the last remnants of semideciduous Atlantic Forest and Cerrado in northeastern São Paulo state, Brazil - Benício, Ronildo Alves; Silva, Fernando Rodrigues da (Biota Neotropica, 2017)
Abstract Although São Paulo state has one of the best known amphibian fauna in Brazil, there are still protected areas for which the species composition remains unknown. Here, we present the first species list of anuran amphibians in Vassununga State Park. This area is one of the last remnants of semideciduous Atlantic Forest and Cerrado in the northeastern region of São Paulo state, southeastern Brazil. To survey species, we visited six sites (two ponds, two streams, and two transects) in December, January, and February of 2014-2015 and 2015-2016, totalizing 18 days of field samplings at each site. We recorded 24 anuran species belonging to four families: Bufonidae (2 species), Hylidae (11 species), Leptodactylidae (10 species), and Microhylidae (1 species). Anurans consist mainly of generalist and widely distributed species. Although none of the species recorded are threatened with extinction according to the International Red List of Endangered Species (IUCN), four species have declining population and another three species have unknown population trends.